Barbastella barbastellus subsp. barbastellus Schreber 1774 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Barbastella barbastellus subsp. barbastellus Schreber 1774 Barbastella barbastellus subsp. barbastellus Schreber 1774, Die Saugethiere, Vol. 1: 168. Type Locality: France, Burgundy. Synonyms: Barbastella barbastellus subsp. barbastelle Müller 1776; Barbastella barbastellus subsp. communis Gray 1838; Barbastella barbastellus subsp. daubentonii Bell 1836. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 480, DOI: 10.5281/zenodo.7316519